Upper extremity and hip range of motion changes throughout a season in professional baseball players - Chan, J. M.; Zajac, J. (The American Journal of Sports Medicine, 2020)
Background: Loss of upper and lower extremity range of motion (ROM) is a significant risk factor for injuries in professional baseball players. Purpose/Hypothesis: The purpose was to determine changes in ROM in professional baseball players over the course of a single season and their careers. We hypothesized that pitchers and position players would lose ROM, specifically total shoulder motion (total ROM [TROM]) and hip internal rotation (IR), over the course of a season and their careers. Study Design: Case series; Level of evidence, 4. Methods: Upper and lower extremity ROM measurements were recorded during pre-, mid-, and postseason on all professional baseball players for a single organization between 2011 and 2018. ROM measurements were compared for pitchers and position players over the course of the season and their careers. Also, ROM measurements over the pre-, mid-, and postseason were compared between pitchers and position players. Results: A total of 166 professional baseball players (98 pitchers, 68 position players) were included. Pitcher hip external rotation (ER; P < .001), IR (P = .010), and TROM (P < .001) for lead and trail legs decreased over the course of the season. Pitcher shoulder ER (P = .005), TROM (P = .042), and horizontal adduction (P < .001) significantly increased over the course of the season. Position player shoulder flexion (P = .046), hip ER (P < .001, lead leg; P < .001, trail leg), and hip TROM (P = .001; P = .002) decreased over the course of the season. Position player shoulder ER (P = .031) and humeral adduction (P < .001) significantly increased over the course of the season. Over the course of pitchers` careers, there was decreased shoulder IR (P = .014), increased shoulder horizontal adduction (P < .001), and hip IR (P = .042) and hip TROM (P = .027) for the lead leg. Position players experienced loss of hip TROM (P = .010, lead leg; P = .018, trail leg) over the course of their careers. Pitchers started with and maintained more shoulder ER and gained more shoulder TROM over a season as compared with position players. Conclusion: Pitchers and position players saw overall decreases in hip ROM but increases in shoulder ROM over the course of the season and career.